Life-Cycles, Dynasties, Savings : Implications for Closed and Small, Open Economies - Faruqee, Hamid (IMF Working Papers; Working Paper ;, 2000)
This paper examines the macroeconomic implications of life-cycle and dynastic saving behavior for closed and small, open economies. Using an extended version of Blanchard's overlapping agents model, the analytical framework nests these two competing views, treating agents as either dynastic households or disconnected generations. Calibrating the life-cycle variant using empirical age-earnings profiles, the analysis compares the long-run effects of fiscal policy shocks under both perspectives. The results quantify the implications of life-cycle considerations for the effects of deficit finance on real interest rates and the capital stock or net foreign assets.